Utilizing the Campus Radio Station in the Communication Research Methods Course - Sims, Judy R. (Broadcast Education Association, 1996)
The purpose of this paper is to provide educators with an example of how the campus radio station can be utilized as a topic of scientific inquiry in an undergraduate communication research methods course. One of the most effective activities for teaching the social scientific process is to provide students with an opportunity to conduct an actual research study. Such an experience promotes and emphasizes active, rather than passive learning. Specifically, this paper shares information about a research project for university students enrolled in an undergraduate communication research methods course; the assignment required students to investigate the attitudes, opinions, and listening behaviors of both community members and university students concerning the campus radio station, WUEC-FM. The methodology of survey was employed, and the investigative strategy of the telephone interview was used to gather data–for example–about music programming preferences, non-music programming (news, public affairs, sports, etc.) preferences, reception, and demographics. The assignment required students to process quantitative and qualitative data using appropriate statistical and coding procedures, analyze and interpret the research results, and write an APA style report (methods, results, and discusson). The assignment served as an excellent vehicle to generate discussion about numerous research related terms and concepts including, for example: survey methodology, questionnaire design, pilot test, ethics, sampling (random, stratified), representativeness, measurement validity, content validity, reliability, measurement error, quantitative and qualitative data, coding, and APA style. Utilizing the campus radio station as the topic of research in the undergraduate communication research methods course can be an extremely rewarding and beneficial individual learning experience for the student. The assignment, which focused on the importance of doing research to understand research, served the needs of students with many different interests in communication and journalism, e.g., radio and/or television broadcasting, programming, management, sales, marketing, public relations, and media research. The project also benefited the management, directors, and programmers of the campus radio station, who were provided with an executive report of the study’s results, which included data concerning the needs and interests of the listening audience as well as information useful in adjusting the station’s format. (Contains Appendix A: Assignment Description and Evaluation Form; Appendix B: Procedure for Choosing a Random Sample, Survey Instructions, Telephone Interview Log and Questionnaire; References).
Paper awarded Second Place in the Open Competition of the Courses and Curricula Division of the Broadcast Education Association.
Keywords: Communication Research Methods; Experiential research; Research Methods course; Researching campus radio; Telephone survey; Telephone interview; Active learning